Examining the Validity of Inquiry-Based Biology Learning Tools in Fostering Critical Thinking Ability - Gusti Ketut Alit Suputra; Rafika Rafika; Effendi Dg Palliwi; Nuraini Nuraini; Khairunnisa Khairunnisa (Jurnal Penelitian Pendidikan IPA, 2023)
Critical thinking skills are essential skills of the 21st century which are very important for students to master. Unfortunately, some research results show students' low critical thinking skills. One important component that supports the teaching of critical thinking for students is learning tools. The results of the preliminary study show the lack of learning tools that are oriented towards students' scientific activities so that it is suspected to be the cause of students' low critical thinking skills. This study aims to evaluate the validity of inquiry-based biology learning tools that can explicitly be used to teach critical thinking skills. This research is descriptive-evaluative research because it only evaluates the results of expert judgment on the validity of the developed learning tools. Two validators with professor qualifications were involved in this study to evaluate the validity of the product using the validation sheet instrument. The results showed that the learning tools developed in the form of lesson plans, learning materials, student worksheets, and critical thinking ability tests were generally stated to be valid (score = 3.65) and reliable (score = 0.93) used to teach students' critical thinking skills in system teaching materials Respiratory. Further research related to the practicality test and the effectiveness of the resulting device needs to be carried out in further research